2022
DOI: 10.18280/ijsse.120509
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Occupational Risk and Personal Protective Equipment on the Example of Ferroalloy Production

Abstract: The objective of this work was to present the results of a comprehensive hygienic assessment of the occupational hazards in the ferroalloy production of a metallurgical plant. For the purpose of evaluating occupational hazards, we used data on the injury potential and occupational agents involved in working conditions, safety indicators for production facilities, occupational diseases, and the provision of workers with personal protective equipment. The assessment of occupational hazards demonstrated that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…To this end, the scientific and methodological literature in the field of occupational safety, regulatory documents, interstate standards, scientific works, and developments of domestic and foreign scientists were analyzed [10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…To this end, the scientific and methodological literature in the field of occupational safety, regulatory documents, interstate standards, scientific works, and developments of domestic and foreign scientists were analyzed [10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…During the research, it was found that the noise levels at workplaces (chargers, smelters, crane operators, senior melting operators, and furnace operators) did not comply with regulatory values, exceeding the permissible level by 5-9 dB. The assessment of occupational risk showed that for each of the investigated professions, the production risk was rated as 3, indicating a moderate risk level -labor conditions class 3.1 [23].…”
Section: Object and Methods Of Researchmentioning
confidence: 97%
“…Previously, it was established by the authors that at the Taraz Metallurgical Plant, workers are exposed to a complex of hazardous environmental factors such as dust, toxic substances, and noise [23].…”
Section: Object and Methods Of Researchmentioning
confidence: 99%
“…The actual state of working conditions at the workplace was determined based on the assessment of the class and degree of harmfulness and danger of the factors of the working environment and work process, as well as the equipment of workers with personal protective equipment (PPE) [17].…”
Section: Object and Methods Of Researchmentioning
confidence: 99%